Pengaruh Keterlibatan dan Kepuasan Kerja terhadap Turnover Karyawan di Perusahaan Minyak Sawit: A Systematic Literature Review - Harditriyono Putra; Muhammad Fajar Nur Iman; Ramlan Ramlan; Bachtiar H. Simamora (Departement of Mathematics Education, 2023)
This literature review aims to examine engagement, job satisfaction, and turnover intention among employees of palm oil companies in Indonesia. Palm oil companies in Indonesia have challenges and problems that impact their performance. Overcoming employee turnover is the main driver that causes the company's performance to decline. This is important to understand because involvement and job satisfaction greatly affect organizational performance. Job engagement and job satisfaction need to be boosted by programs from corporate human resource management. So that employees who work in organizations have higher motivation and better job satisfaction. The main purpose of this article is to explore the influence of involvement and job satisfaction on employee turnover intentions in palm oil companies in Indonesia